1989
DOI: 10.1037/0022-006x.57.6.683
|View full text |Cite
|
Sign up to set email alerts
|

Controlled prospective longitudinal study of women with cancer: I. Sexual functioning outcomes.

Abstract: The incidence and etiology of sexual difficulties for women with survivable cancer were studied. Women with early stage gynecologic cancer (n = 47) were assessed after their diagnosis but prior to treatment and then reassessed at 4, 8, and 12 months posttreatment. Sexual and medical outcomes were compared with data from members of two matched comparison groups who were also assessed longitudinally: women diagnosed and treated for benign gynecologic disease (n = 18) and gynecologically healthy women (n = 57). G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
1
4

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(176 citation statements)
references
References 20 publications
7
164
1
4
Order By: Relevance
“…Strong evidence for the negative impact of medical illness and treatments on sexual functioning exists [7,20,[29][30][31], but concern for sexual matters remains largely on the margin of medical care, particularly for older women. This study presents an extreme case: women who have undergone extirpation, destruction, or severe compromise to their reproductive and sexual organs, many prior to coitarche and reproduction, report that physicians infrequently discussed the impact of their cancer treatment on sexual functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong evidence for the negative impact of medical illness and treatments on sexual functioning exists [7,20,[29][30][31], but concern for sexual matters remains largely on the margin of medical care, particularly for older women. This study presents an extreme case: women who have undergone extirpation, destruction, or severe compromise to their reproductive and sexual organs, many prior to coitarche and reproduction, report that physicians infrequently discussed the impact of their cancer treatment on sexual functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Aging may exacerbate or ameliorate these problems; cancer survivors can feel uncertain about whether sexual problems are a consequence of cancer or aging [6]. Gynecologic and breast cancers and their treatments directly affect the sexual organs and may disrupt the physical and psychological phases of the female sexual response cycle [7,8]. Several studies of shorter-term survivors describe health [9][10][11][12], quality of life [10][11][12] and sexuality [9,10,12] after diagnosis of gynecological cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Here, "survivor" was operationalized as a patient who was at least 6 months post any cancer therapy and diagnosed 2−10 years previously as the clinically relevant interval for the study aims. By at least 2 years, the acute stress of diagnosis has ended (Andersen, Anderson, & deProsse, 1989b), patients have returned to their pre-cancer routines (Guidozzi, 1993;Klee, Thranov, & Machin, 2000a, b), and sexual changes have stabilized (Andersen et al, 1989a). By excluding patients treated longer than 10 years previously, we hoped to decrease the likelihood of added, comorbid conditions common in older adulthood that also disrupt sexuality (Lethbridge-Cejku, Schiller, & Bernadel, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has demonstrated that this global evaluation is sensitive to pre-to post-cancer treatment effects (Andersen et al, 1989a;Andersen, Woods, & Copeland, 1997).…”
Section: Global Sexual Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation